Importance of in Colombia beps (2016)
The following essay has the purpose to analyze the program offered by the National Government called Periodic Economic Benefits (BEPS) and the aids it has for the most vulnerable population in Colombia at levels I, II and III of the Identification System for potential beneficiaries for Social Programs (SISBEN), especially the seniors population which do not count with an income fixed and has low levels of contributions in the Pension System. Periodic Economic Benefits Program (BEPS) is an initiative of the National Government aimed for the 10.8 million Colombians who earn less than a minimum wage and have no guarantee to get a pension, can save up to reach the age of retirement and that way get a 20% subsidy on the saved value and thus achieve a life annuity. BEPS is a program of voluntary savings created under article 155 of the 1151 Act of 2007, which is administered by the Colombian Pension Administrator - COLPENSIONES, and which aims to improve the living conditions of vulnerable elders.